Preparo e caracterização de filmes de sericina e amido modificados com dimetiloluréia,ol ou ácido succínico - Dias, Diego Borelli (2013)
Sericin is a natural silk protein, which is removed from silk in a process called degumming. Sericin recovered can add value to this waste of textile industry and minimize the impact of untreated effluents and solid wastes. While starch is a polysaccharide carbohydrate inexpensive and the most abundant in nature and can be extracted from various plants, such as maize, wheat, potato, cassava, rice, and other plants. Biofilms made by casting using sericin or starch or blend sericin/starch, and the use of glycerol as plasticizer, the films were chemically crosslinked using three types of crosslinking agents in different concentrations (0,1, 0,4 e 0,7 g of crosslinking agents/g of macromolecule), namely: the dimethylolurea (DMU), polyethylene glycol (PEG ) and succinic acid. The films were characterized through the analysis of visual aspects, humidity, water solubility and water vapor permeability, mechanical properties and absorption spectroscopy Fourier transform infrared (FTIR). Films prepared presented visually attractive, with glycerol conferred flexibility to the films. The results for moisture content and solubility were similar to those reported in the literature for biofilms of these polymers. The permeability to water vapor showed values between 2.63 and 17.15 g.mm/m2.dia.kPa. The effects of the increased content of the crosslinking agent used in the films were different between dimethylolurea and polyethylene glycol, especially noticeable difference in the mechanical properties.